Mss11p mediated regulation of transcription, pseudohyphal differentiation and flocculation in Saccharomyces cerevisiae - Franken, Jaco (Cornelius Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.